Are Islamic bonds a safe choice for portfolio diversification in time of crisis? Evidence from volatility-causality analysis of Dubai financial market (Journal of Economics, Law and Society, 2024)
Despite the popularity and uniqueness of Sukuk as an alternative tradable financing tool, the effectiveness of these products in portfolio allocation and diversity is still under constant scrutiny. This paper employs the multivariate BEKK-GARCH (1,1) model to analyse shocks and volatility based on the daily prices of the Dubai Islamic Capital Market (Sukuk Index) and the conventional stock market (DFM Index). Additionally, it applies Johansen co-integration and Granger causality to investigate the persistence of shocks and volatility in long-term relationships, as well as the leading relationship between Islamic and conventional markets. The results validate the impact of their respective news feeds on both Sukuk and stock market indices and demonstrate the persistence of volatility throughout the studied period from April 2009 to December 2020. The causality test reveals a multidirectional relationship effect between Sukuk and stocks, where each is contributing to the other's growth. The study confirms that Sukuk is not a safe haven for portfolio diversification in the Dubai financial market.